Coating doxorubicin‐loaded nanocapsules with alginate enhances therapeutic efficacy against Leishmania in hamsters by inducing Th1‐type immune responses. (25th July 2014) - Kansal, S; Tandon, R; Verma, A; Misra, P; Choudhary, A K; Verma, R; Verma, P R P; Dube, A; Mishra, P R
<x xml:space="preserve">Abstract</x> Background and Purpose The aim of the present study was to evaluate the immunomodulatory and chemotherapeutic potential of alginate‐(SA) coated nanocapsule (NCs) loaded with doxorubicin (SA‐NCs‐DOX) against visceral leishmaniasis in comparison with nano‐emulsions containing doxorubicin (NE‐DOX). Experimental Approach NE‐DOX was prepared using low‐energy emulsification methods. Stepwise addition of protamine sulphate and SA in a layer‐by‐layer manner was used to form SA‐NCs‐DOX. SA‐NCs‐DOX, NE‐DOX and Free DOX were compared for their cytotoxicity against Leishmania donovani‐infected macrophages in vitro and generation of T‐cell responses in infected hamsters in vivo. Key Results Size and ζ potential of the NE‐DOX and SA‐NCs‐DOX formulations were 310 ± 2.1 nm and (−)32.6 ± 2.1 mV, 342 ± 4.1 nm and (−)29.3 ± 1.2 mV respectively. SA‐NCs‐DOX was better (1.5 times) taken up by J774A.1 macrophages compared with NE‐DOX. SA‐NCs ‐DOX showed greater efficacy than NE‐DOX against intramacrophagic amastigotes. SA‐NCs‐DOX treatment exhibited enhanced apoptotic efficiency than NE‐DOX and free DOX as evident by cell cycle analysis, decrease in mitochondrial membrane potential, ROS and NO production. T‐cell responses, when assessed through lymphoproliferative responses, NO production along with enhanced levels of iNOS, TNF‐α, IFN‐γ and IL‐12 were found to be up‐regulated after SA‐NCs‐DOX, compared with responses to NE‐DOX in vivo. Parasitic burden was decreased in Leishmania‐infected hamsters treated with SA‐NCs‐DOX, compared with NE‐DOX. Conclusions and Implications Our results provide insights into the development of an alternative approach to improved management of leishmaniasis through a combination of chemotherapy with stimulation of the innate immune system.